Patient and Physician Expectations of Add‐On Treatment With Golimumab for Rheumatoid Arthritis: Relationships Between Expectations and Clinical and Quality of Life Outcomes1. Issue 12 (December 2014) - Dasgupta, Bhaskar; Combe, Bernard; Louw, Ingrid; Wollenhaupt, Jürgen; Zerbini, Cristiano A. F.; Beaulieu, Andre; Schulze‐Koops, Hendrik; Durez, Patrick; Wolff, Verónica; Yao, Ruji; Weng, Haoling H.; Govoni, Marinella; et al.
<x xml:space="preserve">Abstract</x> Objective Rheumatoid arthritis (RA) management involves improving clinical outcomes and quality of life (QOL). Golimumab is used as add‐on therapy for patients who have failed disease‐modifying antirheumatic drugs (DMARDs). This GO‐MORE subanalysis investigated relationships between patient and physician expectations and outcomes. Methods GO‐MORE was an open‐label, multinational, prospective study in biologic agent–naive patients with active RA despite DMARD treatment. Patients received 50 mg subcutaneous golimumab monthly for 6 months. At baseline and month 3, patients rated treatment expectations for the following 3 months using 5‐point scales (where 1 = good and 5 = poor). Outcomes were compared among expectation tertiles: most positive, intermediate, and least positive. At baseline and month 3, physicians predicted patient disease state 3 months later. Results At baseline, 3, 280 efficacy‐evaluable patients with moderate (21.3%) or high (78.7%) disease activity had mean ± SD disease duration of 7.6 ± 7.9 years, mean ± SD Health Assessment Questionnaire (HAQ) disability index (DI) score of 1.44 ± 0.67, and mean ± SD EuroQol 5‐domain (EQ‐5D) score of 0.42 ± 0.33. Patients reported high treatment expectations (mean 1.43); 95.9% expected golimumab to be better than current treatment. Patients with fewer DMARD failures, higher disease activity, shorter disease duration, younger age, and female sex reported higher expectations (P < 0.05 for all). After 6 months, patients with the most positive expectations had higher remission rates (P < 0.0001) and greater HAQ DI (P < 0.0001) and EQ‐5D (P < 0.0001) score improvements. At baseline, physicians expected 29.6% and 59.2% of patients to attain remission and low disease activity, respectively, after 3 months. Conclusion Patients had high expectations for golimumab treatment. Patients with more positive expectations had greater remission rates, improvements in function, and QOL.